2022
DOI: 10.1002/nau.24903
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of capacitive resistive monopolar radiofrequency in the physiotherapeutic treatment of chronic pelvic pain syndrome: A randomized controlled trial

Abstract: Aim To evaluate the efficacy of adjuvant, capacitive resistive monopolar radiofrequency (CRMRF, INDIBA) treatment at 448 kHz together with physiotherapeutic techniques compared to a sham treatment with the same techniques, for pain reduction and quality of life (QoL) improvements in patients with chronic pelvic pain syndrome (CPPS). Methods A triple‐blind, randomized controlled trial (RCT) including patients with CPPS randomly allocated (1:1) to a CRMRF‐activated group (intervention) or a CRMRF‐deactivated one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…ESWT has demonstrated efficacy in CPPPS treatment offering noninvasive, positive long-term outcomes. Notably, patients with higher initial NIH-CPSI scores and psychosocial history respond well to ESWT [41][42][43]. CRMRF is superior over sham treatment, reducing pain and enhancing CPPPS patients' quality of life.…”
Section: New Management Optionsmentioning
confidence: 98%
“…ESWT has demonstrated efficacy in CPPPS treatment offering noninvasive, positive long-term outcomes. Notably, patients with higher initial NIH-CPSI scores and psychosocial history respond well to ESWT [41][42][43]. CRMRF is superior over sham treatment, reducing pain and enhancing CPPPS patients' quality of life.…”
Section: New Management Optionsmentioning
confidence: 98%
“…Another anti-inflammatory physical strategy [4], based on the non-invasive application of radiofrequency currents at 448 kHz, is the capacitive resistive electrical transfer (CRET). the biomechanisms involved in the potential anti-inflammatory CRET effects are not yet sufficiently investigated, previous studies by our group have revealed that intermittent, subthermal CRET stimulation promotes the proliferation of various types of human cells, including stem cells [5], keratinocytes, and fibroblasts, as well as migration of human fibroblasts [6].…”
Section: Introductionmentioning
confidence: 99%